2021
DOI: 10.15407/socium2021.02.140
|View full text |Cite
|
Sign up to set email alerts
|

Discourse-structure of social cohesion as a category of social policy: experience of critical discourse-analysis application

Abstract: The article is dedicated to identifying the discourses of social cohesion as a category of social policy, constructed by the textual structures of national governments, intergovernmental associations and international organisations documents. The paper is performed in the frame of a discourse-analytical approach; discursive events define the normative acts of national governments, intergovernmental associations, and international organizations during the 90s – 2000s, devoted to the issue of social cohesion; de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Це може стати суттєвою перешкодою для посилення соціальної згуртованості українського суспільства, оскільки соціальний капітал є одним з ключових компонентів соціальної згуртованості. Разом з тим, акцент на подоланні нерівностей виправданий, оскільки розподіляє соціальну відповідальність між державою («інституціями» посилення соціальної згуртованості на соцієтальному рівні) та різними іншими соціальними суб'єктамиспільнотами (що у взаємодії відтворюють соціальну згуртованість українського суспільства на рівні «особа-спільнота») [7].…”
Section: Social Cohesion As a Social Economic And Management Phenomen...unclassified
“…Це може стати суттєвою перешкодою для посилення соціальної згуртованості українського суспільства, оскільки соціальний капітал є одним з ключових компонентів соціальної згуртованості. Разом з тим, акцент на подоланні нерівностей виправданий, оскільки розподіляє соціальну відповідальність між державою («інституціями» посилення соціальної згуртованості на соцієтальному рівні) та різними іншими соціальними суб'єктамиспільнотами (що у взаємодії відтворюють соціальну згуртованість українського суспільства на рівні «особа-спільнота») [7].…”
Section: Social Cohesion As a Social Economic And Management Phenomen...unclassified
“…Проведений аналіз розробленості проблематики в науковій літературі показав, що на сьогодні вже накопичено теоретичний і емпіричний матеріал з проблеми, яка інтенсивно досліджується в напрямі пошуку шляхів забезпечення ефективності процесу розвитку соціальної активності молоді, зокрема від час її освіти. Розкриваючи зміст цього поняття з аналізу документів Європейського Союзу [7], а також глибинних витоків змісту у порівнянні з іншими близькими за змістом суміжними поняттями [8], О. Дейнеко підтримує висновок М. Краська [9] щодо актуальності позиціонування соціальної згуртованості як діяльнісного «етапу» розвитку соціальної солідарності, в основі якоїсистемні внутрішньогрупові взаємодії. Ураховуючи те, що будь-які зв'язки у суспільних відносинах підлягають нормативному регулюванню, важливим процесом у соціальному вихованні виступає забезпечення опанування нормами відносин, формування позитивного Соціальна згуртованість суспільства в умовах глобальних викликів покликана дати відповідь на питання «як жити разом».…”
Section: Development Of Social Activity Of Youth Students As the Basi...unclassified
“…High trust in the president is a major reversal from the previous year (from 21% in December 2021 to 84% in 2022). Recent research has also identified the positive effects of the decentralisation reforms with respect to strengthening social cohesion in Ukraine [21]. Finally, Ukraine is increasingly committed to democratic development -95% percent of respondents to an August 2022 nationwide poll indicated that it is 'very important' or 'important' for them that Ukraine becomes a fully functioning democracy (an increase from 76% the previous year) [22].…”
Section: Governance Identity Trust and The Social Fabricmentioning
confidence: 99%